2016
DOI: 10.1080/10503307.2016.1246769
|View full text |Cite
|
Sign up to set email alerts
|

Treatment engagement in the early phase of cognitive-behavior therapy for panic disorder: A grounded theory analysis of patient experience

Abstract: Exposure-based cognitive-behavior therapy (EBCBT) is the treatment of choice for panic disorder (PD). However, little is known about early treatment processes that facilitate retention in treatment and positive outcomes of PD treatment. We studied the development of early treatment process with semi-structured individual in-depth interviews with 12 patients with PD, conducted post session 3. Grounded theory was used to analyze the transcripts. The development of early treatment process was captured by four the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…A qualitative study that examined the experiences of patients with PD+/-Ag, suggested that understanding the individual factors that maintain the disorder during the first BT sessions, is a key component for patients' subsequent therapeutic involvement. 9 The successful manualized exposure-based BT of patients with PD+/-Ag in a single session, accompanied by personalized self-help manual, 10 has confirmed the usefulness of active participation in the treatment outcome. Moreover, their emotional and functional gains and reduced relapses in long-term evaluations, may be due to this experiential training and empirical feedback, which seems to significantly modify the attribution of mental health locus of control.…”
Section: Discussionmentioning
confidence: 86%
“…A qualitative study that examined the experiences of patients with PD+/-Ag, suggested that understanding the individual factors that maintain the disorder during the first BT sessions, is a key component for patients' subsequent therapeutic involvement. 9 The successful manualized exposure-based BT of patients with PD+/-Ag in a single session, accompanied by personalized self-help manual, 10 has confirmed the usefulness of active participation in the treatment outcome. Moreover, their emotional and functional gains and reduced relapses in long-term evaluations, may be due to this experiential training and empirical feedback, which seems to significantly modify the attribution of mental health locus of control.…”
Section: Discussionmentioning
confidence: 86%
“…In the testing phase, these requirements and behaviors will be systematically tested in real-world scenarios in the Child and Family Center. In health care communication settings, it is especially important that the child feels comfortable enough to share all necessary information with the caregiver, in order to provide the appropriate and most effective care possible (e.g., [17]). When looking at child-robot communication in the health care field, it is therefore essential to create a context of trust and safety, facilitating a bond between child and robot.…”
Section: Testing Phasementioning
confidence: 99%
“…These communication aspects contribute to the enrichment of the the child-robot interaction and personalization of the treatment (e.g., [3]). Consequentially, since the social robot will in this way be able to better understand the child, it might stimulate trust and bonding in the child-robot relationship, which is essential for a successful therapeutic treatment (e.g., [17]).…”
Section: Introductionmentioning
confidence: 99%
“…In such health care communication settings, it is important that the child feels comfortable enough to share all necessary information with the caregiver (e.g., [20]). More specifically, it is essential to create a context of trust and safety, facilitating a bond between child and robot.…”
Section: Research Questions and Approachmentioning
confidence: 99%